KOMORBIDITAS PENYANDANG CEREBRAL PALSY DI KOMUNITAS CEREBRAL PALSY METRO - Khasanah, Al Um Aniswatun; Yudistira, Efraldo; Akbar, Bota Muhammad; Dewi, Anak Ayu Nyoman Trisna Nata (Universitas Muhammadiyah Metro, 2022)
The condition of one of the disabled people is various, one of which is Cerebral Palsy. Most children with Cerebral Palsy have at least one comorbid disorder or comorbidity. In the SCPE data, the most common comorbidities found were language disorders (71%), followed by intellectual disorders (62%), epilepsy (39%), and visual disturbances (22%). The survival of patients who depend on the severity of disability experienced in the Cerebral Palsy Metro community. Design This study is a descriptive analytic study using a cross sectional or cross-sectional design. In the cross sectional design used a transverse approach, where observations of the independent variable and the dependent variable were carried out only once at the same time. With a total sample of 50. The research subjects were 31 men (62%) and 19 women (38%), with a sample of age range between 0-18 years. Most participants were in the type of Spastic Quadriplegia CP. Outcomes of Comorbid Cerebral Palsy in study subjects. Intellectual disability is 30 (60%), Epilepsy is 19 (38%), Visual impairment is 3(6%), Speech disorder is 37(74%), Development and growth disorders is 14(28%), Defecation disorders 10 (20% ), Respiratory Disorders 4 (8%), Orthopedic disorders Ankle deformities 23(46%), Scoliosis deformity disorders 21 (42%), Hip subluxation disorders 9(18%), Sleep disturbances 11 (22%), which were individual Cerebral Palsy has at most three comorbidities and is mostly owned by the Spastic Quadriplegia CP type. Comorbidities in people with cerebral palsy in the metro cerebral palsy community were the most common in speech disorders and more than three comorbidities were found in cerebral palsy individuals with the type of spastic Quadriplegia CP.